Pengelolaan Pelabuhan Perikanan Samudera Kendari Berwawasan Lingkungan Berdasarkan Aspek Ekologi - Taher, Muh Ikhsan; Tadjuddah, Muslim; Kamri, Syamsul; Alimina, Naslina; Mustafa, Ahmad; Abdullah, Abdullah (PekaBuana : Jurnal Ilmiah Teknologi dan Manajemen Perikanan Tangkap, 2023)
Kendari PPS Ocean Fishing Port is an integrated fishing industry center in eastern Indonesia and especially in Southeast Sulawesi. Having high activity and productivity makes the port face environmental problems. The current problem at Kendari PPS is that there is still some plastic waste in the harbor pool, ship activity mooring at Kendari PPS causing used waste in the harbor pool and other problems, namely the decline in environmental quality due to activities at Kendari PPS. Based on these problems, it is necessary to make changes regarding the environmental conditions of the port through an assessment of the conditions in the Kendari PPS. This research aims (1). Knowing the status of environmental management in PPS Kendari based on ecological aspects. The research was conducted in November 2022 - January 2023 with data collection locations at the Kendari Ocean Fishing Port. The approach used to overcome the problems in this study is to examine environmental management conditions by giving a score from each analysis to measure parameters that are in accordance with the eco-fishingport concept. The results showed that the Kendari PPS environmental management status was based on the concept of eco-fishingport parameters on the ecological aspect, that is, of the three parameters of the ecological aspect, only the green open space (RTH) parameter did not meet the eco-fishingport concept and the port pool water quality parameters needed to be increased so as to achieve eco-fishing port concept. PPS Kendari needs to prioritize improving port management which is considered a priority, such as controlling and monitoring the quality of the harbor pond waters, as well as adding tree planting in vacant land areas to add a calm and comfortable impression.